2010
DOI: 10.1038/nature08708
|View full text |Cite
|
Sign up to set email alerts
|

Increasing springtime ozone mixing ratios in the free troposphere over western North America

Abstract: In the lowermost layer of the atmosphere-the troposphere-ozone is an important source of the hydroxyl radical, an oxidant that breaks down most pollutants and some greenhouse gases. High concentrations of tropospheric ozone are toxic, however, and have a detrimental effect on human health and ecosystem productivity. Moreover, tropospheric ozone itself acts as an effective greenhouse gas. Much of the present tropospheric ozone burden is a consequence of anthropogenic emissions of ozone precursors resulting in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
363
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 414 publications
(397 citation statements)
references
References 29 publications
29
363
4
1
Order By: Relevance
“…Chan and Vet (2010) used a muti-site cluster analysis and also found a significant upward trend in background ozone along the west coast of North America. Similar trends have been identified in free tropospheric measurements through a comprehensive integration of data from multiple years and west coast studies (Cooper et al, 2010). Reasons for these trends are unclear and several possibilities have been suggested including regional continental or ship emissions, biomass burning and trans-Pacific transport (Cooper et al, 2010;Jaffe and Ray 2007;Dalsoren et al, 2010;Jaffe, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…Chan and Vet (2010) used a muti-site cluster analysis and also found a significant upward trend in background ozone along the west coast of North America. Similar trends have been identified in free tropospheric measurements through a comprehensive integration of data from multiple years and west coast studies (Cooper et al, 2010). Reasons for these trends are unclear and several possibilities have been suggested including regional continental or ship emissions, biomass burning and trans-Pacific transport (Cooper et al, 2010;Jaffe and Ray 2007;Dalsoren et al, 2010;Jaffe, 2010).…”
Section: Introductionmentioning
confidence: 65%
“…Factors related to the measurements or their use include: uncertainties in early measurements (e.g., Staehelin et al, 1994;Logan et al, 2012;TOAR-Observations); sampling biases in modelmeasurement comparisons, such as the representativeness of the trends derived from sparse measurements (Cooper et al, 2010;Lin et al, 2015a); and the presence of trends driven by low-frequency climate variability that freerunning CCMs are not expected to reproduce exactly (Lin et al, 2014(Lin et al, , 2015bBarnes et al, 2016;Garcia-Menendez et al, 2017). Factors related to the models include: errors in the trends incorporated in the underlying emission inventories used in the model (Granier et al, 2011;Hassler et al, 2016); limitations of coarse-resolution models in resolving observed baseline conditions (Lin et al, 2017); and weaknesses in the model representation of the processes (chemical, physical, and dynamical) that control the observed trend at a given location.…”
Section: State Of Knowledgementioning
confidence: 99%
“…Furthermore, global emissions of greenhouse gases and other pollutant precursors are projected to increase (IPCC, 2007). Moreover, recent research has provided evidence of increasing long-range transport of O 3 and PM 2.5 precursors from Asia and their influence over the western US (Lelieveld and Dentener, 2009;Wuebbles et al, 2007;Cooper et al, 2010Cooper et al, , 2012Zhang et al, 2010;Ambrose et al, 2011;WMO, 2012;Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%